A simple model for preliminary evaluation of rainfall-induced slope instability - Lee, Min Lee (2011)
Slope failures in the tropical regions, particularly Malaysia are commonly triggered by frequent rainfall. The tropical rainfall can be characterized as short and intense throughout the year, and prolonged and less intense during monsoon seasons. Under such circumstances, various rainfall patterns should be included in the analysis of rainfall-induced slope failure in the tropical regions. This paper is aimed to demonstrate a simple model for preliminary evaluation of rainfall-induced slope failure. The critical rainfall patterns for four typical types of soil were first determined. Seepage finite element analyses were conducted using the extreme rainfall of ten-year return period for Johor Bahru, Malaysia. The results showed that the ratio of rainfall intensity to soil saturated permeability (i.e., I/ksat) plays an important role in determining the critical rainfall pattern. Two critical combinations of antecedent rainfall and major rainfall, 1-day, 2-day, 3-day, 5-day, 7-day, 14-day, and 30-day antecedent rainfalls and the redistribution of the critical combination of antecedent rainfall and 1-day major rainfall were responsible for the formation of suction envelope in soil. The suction envelope, representing the worst suction distribution in soil, was used for the computation of factor of safety of soil slope through the modified infinite-slope–limit-equilibrium method. A model, PERISI, was developed based on the findings from numerical simulation. The suction envelope and factor of safety computed from the PERISI model showed good agreements with the results obtained from Seep/W and Slope/W computer programs and the results derived from the model of Rahardjo et al. developed in 1995.